Physiological and growth analysis and productivity of cassava under irrigation levels - Silva, Ricardo Barros; Teodoro, Iêdo; Souza, José Leonaldo de; Ferreira Júnior, Ricardo Araújo; Santos, Marcos Alex dos; Magalhães, Ivomberg Dourado; Lyra, Guilherme Bastos; Morais, Marcos Antônio Ferreira de; Teodoro, Iêdo Peroba de Oliveira; Santos Neto, Antônio Lucrécio dos; Martins, Gleica Maria Correia (Revista de Ciências Agroveterinárias, 2022)
The objective of this research was to evaluate the growth, productivity and the physiological responses of cassava under irrigation levels in the Alagoas Forest Zone. The statistical design used was randomized blocks, in a split-plot scheme, with four replications. The treatments were six levels of irrigation, depending on the evapotranspiration of the crop – ETC (L0 = 0% (Rainfed), L1 = 40%, L2 = 80%, L3 = 120%, L4 = 160% and L5 = 200% of the ETC). The variables were divided into groups: growth and production (evaluated in six bimonthly periods - 1 year) and the physiological (net photosynthetic rate and transpiratory, leaf temperature, stomatal conductance, instantaneous water use efficiency, potential quantum yield, effective quantum efficiency of photosystem II and SPAD index were evaluated in five bimonthly periods – 10 months). The water balance of the irrigation levels was carried out, on a decendial scale. The annual evapotranspiration of cassava added around 1,030 mm, and in dryland areas, the effective rainfall is only 522 mm, which generates a water deficit of 508 mm, and this makes the importance evident of use of irrigation in crops in the region. In general, cassava growth, yield and the physiological responses are superior in irrigated areas when compared with the rainfed crops, and irrigation provides the root and total biomass yields of 97 and 155 Mg ha-1, under the irrigation levels of 129 and 136% of the ETC, respectively, in the studied region.